Colours for medicinal purposes: a crossroads between the West and Africa - (:unkn) unknown (My University, 2020)
Humanity uses colors in many major ways, such as signage (non-verbal semantics), expression of identity, art, food or medicine. Traditionally, Europe had used colors as aids to developing a clinical diagnosis, while Africa has used colors primarily in the stages of care. While the West has recently rediscovered the impact of colors on health, many societies in Africa have been using them for several generations. Thus, the study of the modes of use of color in customary medicines in Africa presents a renewed challenge for the health of humanity. Amulets, body paints, dance costumes, medicine tinctures, mourning ornaments and large funerals, illustrate the diversity of uses of colors to protect or cure ailments. This article is not intended to assess the relevance of colored solutions but to illustrate the multiplicity of relations between medicine and colors on these two geographical areas, and to explain the reasons for different uses by historical conceptions of medicine in Europe and in Africa.
Keywords: African Research